2015
DOI: 10.1007/s10140-015-1332-7
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric trauma care with computed tomography—criteria for CT scanning

Abstract: Trauma centers, trauma management concepts, as well as integration of whole-body computed tomography (CT) reduced mortality significantly. The accuracy of a trauma care algorithm with emergency CT in children was evaluated. Data of 71 children with emergency CT were recorded retrospectively. In addition to epidemiological data admission date, kind of CT scan, mechanism of injury, missed diagnoses, injury severity score (ISS), admission to and time on intensive care unit (ICU), and time of hospitalization were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 38 publications
(45 reference statements)
0
6
0
3
Order By: Relevance
“…Our standard protocol group had a lower mean ISS, which could be due to injury mechanisms leading clinicians to opt for WBCT. Although reports about adult cohorts suggest that the mechanism of injury alone should not be an indication for using WBCT [7,33,41]. Judicious use of CT is of high importance and as with any test, the possibility of a false positive result must be considered [38].…”
Section: Discussionmentioning
confidence: 99%
“…Our standard protocol group had a lower mean ISS, which could be due to injury mechanisms leading clinicians to opt for WBCT. Although reports about adult cohorts suggest that the mechanism of injury alone should not be an indication for using WBCT [7,33,41]. Judicious use of CT is of high importance and as with any test, the possibility of a false positive result must be considered [38].…”
Section: Discussionmentioning
confidence: 99%
“…However its high cost and ionizing radiation used on CT that is potentially harmful especially for children are the main handicaps of CT (11). Recently, Muhm et al (12) reported that; among 71 children admitted to the emergency department due to a trauma; 67.6% received a cranial scan and only one third of the children had had relevant trauma related findings in the CT scan. In our study CT scan was obtained in 63 (31.5%) cases and revealed pathology in only 3 of them.…”
Section: Discussionmentioning
confidence: 99%
“…11 Our figures compared favourably with figures from studies by Fenton et al and Muhm et al, which reported lower figures of 46% and 33.8% for positive CT findings in paediatric trauma patients. 12,13 This demonstrates that CT scans are being used judiciously in our institution in this context, which may help to ameliorate the burden of paediatric bicycle injuries on the healthcare system and on patients who sustain these injuries. A quarter of our patients required inpatient admission, with 7 (8.6%) patients being admitted to either HD or ICU.…”
Section: Discussionmentioning
confidence: 99%